Social Criticism in Jane Austen s Persuasion - May Witwit; Maysoon Taher Muhi (PROSPECTIVE RESEARCHES, 2023)
In Persuasion, Jane Austen offers a penetrating critique of the standards of the British class system. She criticizes a system based on social distinctions and definitions like Superior and Inferior. Through irony and satire, she vividly shows Victorian class rigidity and its traditional values. This paper aims at showing that through her realistic portrayal of families and characters; Austen manages to capture the major defects of her social circle and sets to expose them one by one.